Effects of P1G10 against UVB-induced damage: Reduction of antioxidant stress, inflammation and cell proliferation - Kátia M. Freitas; Emerson S. Veloso; Ênio Ferreira; Marcelo V. Caliari; Carlos E. Salas; Miriam T.P. Lopes (Journal of Photochemistry and Photobiology)
Background: P1G10 is the proteolytic fraction from Vasconcellea cundinamarcensis latex equivalent to papain from C. papaya. It acts as healing enhancer in diverse wound scenarios. In a preliminary study P1G10 showed promising anti-inflammatory activity in lesions induced by single dose UVB irradiation. Aim: The present study assesses the impact of P1G10 topically applied on mice lesions induced by multiple UVB doses. Results: After repeated exposure to 240 mJ cm-2 UVB, P1G10 decreased by ∼50 % the detected ROS, enhanced glutathione peroxidase (GPx) and catalase activities, thereby protecting against oxidative stress. The anti-inflammatory effect of the fraction was consolidated by reduction in TNF-α (∼70 %) and IL1β (∼90 %) and confirmed by histological analyses showing a reduction in cellularity and leukocyte infiltration into the hypodermis. Additionally, epidermal hyperplasia induced by UVB was reduced as shown by a decrease of PCNA immunolabeling in keratinocytes. Pathways involved in the inflammatory process and in UVB-induced production of free radicals were also affected, revealing that P1G10 application reduced phosphorylation of MAP kinase proteins (JNK and P38) and Akt, as well as MMP-9 activity. Conclusions: These data confirm the lasting protective action of P1G10 by moderating oxidative stress and apoptosis induced by multiple doses of UV-B in the skin, suggesting a potential preventive action against the onset of carcinogenesis.